The Level of Anger Among Couples During the Coronavirus Pandemic in the Northern Region - Salameh, Maram Jasser Salem Bani (International Journal of Membrane Science and Technology, 2023)
This paper aimed to investigate the level of anger among spouses during the Corona pandemic (COVID-19) in the northern region of Jordan. The descriptive analytical approach was used, and to collect data, the researcher adopted the Anger Management Scale (AMS) (Stith & Hamby, 2001). The scale consisted of (32) items distributed over four areas (Escalating Strategies, Negative Attributions, Calming Strategies, and Self-Awareness). A total of (406) couples from the northern governorates were recruited in this study. Statistically significant differences were found for the effect of the number of years of marriage, favouring the category (more than ten years). In addition, the number of children demonstrated statistically significant differences favouring the category of (more than (6) children). However, no statistically significant differences were attributable to educational qualification.